Caffeine Use Disorder: A Review of the Evidence and Future Implications - Addicott, Merideth A. (2014)
The latest edition of the Diagnostic and Statistical Manual (DSM-5) has introduced new provisions for caffeine-related disorders. Caffeine Withdrawal is now an officially recognized diagnosis, and criteria for caffeine use disorder have been proposed for additional study. caffeine use disorder is intended to be characterized by cognitive, behavioral, and physiological symptoms indicative of caffeine use despite significant caffeine-related problems, similar to other Substance Use Disorders. However, since nonproblematic caffeine use is so common and widespread, it may be difficult for some health professionals to accept that caffeine use can result in the same types of pathological behaviors caused by alcohol, cocaine, opiates, or other drugs of abuse. Yet there is evidence that some individuals are psychologically and physiologically dependent on caffeine, although the prevalence and severity of these problems is unknown. This article reviews the recent changes to the DSM, the concerns regarding these changes, and some potential impacts these changes could have on caffeine consumers.